TEACHING VOCABULARY THROUGH HOT SEAT TO YOUNG LEARNERS - Hartini Agustiawati (Global Expert: Jurnal Bahasa dan Sastra, 2022)
English is so global in the world. Teaching English as foreign language is not easy. It needs motivation, spirit and willingness. Especially young learners, they have no area to speak and practice. That condition makes serious effect. In order to improve students’ speaking ability, teacher must ask them to memorize and learn Vocabulary. Unfortunately, it is a big problem to persuade students to read and memorize it. Vocabulary is the most important element in learning English. Teaching vocabulary is challenging to young learners. It will be boring without method, games and interesting technique. As an instructor, teacher or lecturer must find out a strategy to face this condition. We should create simple way but interesting to our students. In order to help young learners to learn vocabulary, we can use easy and simple game. So, Hot seat can be a solution to learn vocabulary. It is suitable to young learners and easy to use. Students can memorize the words and have fun in learning.